SIKAP BAHASA SISWA SMAN 2 GUNUNGPUTRI TERHADAP BAHASA INDONESIA DALAM KOMUNIKASI TULIS MELALUI GRUP WHATSAPP - Tomi Nugraha (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to discuss the language attitudes to students of SMA Negeri 2 Gunugputri towards Indonesian in written communication with the Whatsapp group . This study used a qualitative descriptive method . The data collection techniques used were speech-free listening and note-taking techniques . The results of the analysis show that the language attitudes to SMA Negeri 2 Gunungputri students have diverse language attitudes to Indonesian , regional languages , and foreign languages . The respondent's language attitude to Indonesian in the three components is very positive about an index of 3.36 . It can be interpreted that SMA Negeri 2 Gunungputri students have a very good knowledge of Indonesian . The knowledge possessed by students is in line with their affective and conative components . The choice of language attitudes to students of SMA Negeri 2 Gunungputri has an impact on language shifts among students . This can be seen from the communication process of the class whatsapp group conversation . They are more comfortable using Indonesian slang by combining language code mixing and language code switching with regional languages and English . The factors of the choice of language attitudes to this study lie in the sociolinguistic context .